Clinical profile and outcome in neonates born to COVID-19 positive mothers and COVID positive children aged between 1 month to 12 years admitted in a tertiary COVID care centre: a cross sectional study - N., Madhavi; Mohan, Madan M.; Padma, Jhansi K.; Vijayalakshmi, Venkata V. (International Journal of Contemporary Pediatrics, 2022)
Background: COVID-19 pandemic has caused worldwide havoc since the first case was discovered in China in December 2019. The infection has caused less severe infections and fewer deaths in children compared to adults. During the first two waves of COVID-19, the mortality rate in children has been <3% in India though more severe infections and hospitalizations were seen during the second wave. This study was undertaken at a tertiary Pediatric COVID care center during the third wave to understand the clinical, morbidity profile and outcomes in neonates born to COVID positive mothers and children who are COVID positive. Methods: Neonates born to COVID positive mothers and children between the age group 1 month to 12 years admitted in Government general hospital, Kakinada, Andhra Pradesh from 1January 2022 to 31March 2022 were included in the study. Their demographic, clinical, morbidity profile, treatment details were noted and outcomes observed. Results: All neonates were found to be RTPCR negative. 28% of neonates were born prematurely and 16% had birth asphyxia. Respiratory distress was the most presenting symptom. Death was seen in 4 newborns due to perinatal complications. More children less than 10 years required admission.15% of children were asymptomatic. Fever, cough, and running nose were the most presenting complaints. 2 children who had co-morbidities at the time of admission died. Conclusions: The third wave of COVID-19 did not cause any significant change in morbidity and mortality in children compared to the previous two waves.